Influence of intimate partner violence on behaviour, psychological status and school performance of children - Jayasinghe, R.M.S.D.F (My University, 2006)
The study aimed to determine the influence of IPV on behavior, psychological status and school performance of children. Cross sectional analytical study design. was used to achieve the objectives. The exposure (IPV) was assessed in mothers and the outcome was assessed in children. Sample consisted of 828 Sinhalese speaking school children of 14-17 years of age and their mothers who were residing in the Chilaw MOH area of the Puttlam district. The prevalence of abnormal behavior and psychological status among the children was 21.0 percent. The commonest domain was hyperactivity and the least frequent domain was conduct problems. The school attendance was more than 80 percent in 663 percent of children and nearly 80 percent of children have obtained average marks of more than 40 percent. The percentage of ever IPV was 31.2 percent while that of current IPV was 21.0 percent. The percentage of current sexual abuse was 43 percent. A significant association was observed between current IPV and abnormal behavior and psychological status of children. For abnormal behavior and psychological status, current IPV, regular consumption of alcohol by the father, past and family history of psychological illness.